Practical Teaching of Clinical Gene Amplification Testing in Laboratory Medicine Education: Experiences and Insights - Meng, Xianchun; Zhang, Shijie; Liu, Yuying (Journal of Research in Vocational Education, 2025)
The field of laboratory medicine education has significantly evolved, with clinical molecular biology testing techniques now a core part of undergraduate medical laboratory curricula. These courses equip students with essential knowledge and skills for modern diagnostics. The COVID-19 pandemic accelerated the establishment of clinical gene amplification testing laboratories globally. These laboratories, crucial for nucleic acid testing and other molecular diagnostics, enhanced healthcare facilities' capabilities during the pandemic and created opportunities for improving practical teaching in laboratory medicine education. Effective clinical instruction in these laboratories during internships is vital. It helps students understand theoretical knowledge related to clinical molecular biology testing, master common techniques in clinical gene amplification testing, and develop the ability to apply molecular biology testing results in clinical diagnosis, treatment monitoring, and prognosis evaluation. This improves the quality of laboratory medicine education and meets the demand for specialized professionals.